Optical alignment and confinement of an ellipsoidal nanorod in optical tweezers: a theoretical study - Trojek, Jan; Chvátal, Lukáš; Zemánek, Pavel (Journal of the Optical Society of America. A, Optics, image science, and vision, 2012)
Within the Rayleigh approximation, we investigate the behavior of an individual ellipsoidal metal nanorod that is optically confined in three dimensions using a single focused laser beam. We focus on the description of the optical torque and optical force acting upon the nanorod placed into a linearly polarized Gaussian beam (scalar description of the electric field) or a strongly focused beam (vector field description). The study comprises the influence of the trapping laser wavelength, the angular aperture of focusing optics, the orientation of the ellipsoidal nanorod, and the aspect ratio of its principal axes. The results reveal a significantly different behavior of the nanorod if the trapping wavelength is longer or shorter than the wavelength corresponding to the longitudinal plasmon resonance mode. Published experimental observations are compared with our theoretical predictions with satisfactory results.